2018
DOI: 10.1177/0284185118770918
|View full text |Cite
|
Sign up to set email alerts
|

Motion artifacts, lesion type, and parenchymal enhancement in breast MRI: what does really influence diagnostic accuracy?

Abstract: Motion artifacts can impair lesion characterization with breast MRI, but lesion type and small size have the strongest influence on diagnostic estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
(52 reference statements)
1
14
1
1
Order By: Relevance
“…This may reflect different kind of considered motion artifacts, as Fiaschetti et al (12) reported artifacts affecting image interpretation, without any grading scale. In fact, considering only cases in which a reduction in image quality hindered image interpretation (grade 3), our rate of motion artifacts decreases to 8%, independently from breast MRI indication and similarly to the 9% rate of moderate/marked motion artifacts reported by Clauser et al (9). This relatively low rate of motion artifacts should be considered as linked to the patient prone position used in state-of-the-art breast MRI that minimizes respiratory movement (13).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This may reflect different kind of considered motion artifacts, as Fiaschetti et al (12) reported artifacts affecting image interpretation, without any grading scale. In fact, considering only cases in which a reduction in image quality hindered image interpretation (grade 3), our rate of motion artifacts decreases to 8%, independently from breast MRI indication and similarly to the 9% rate of moderate/marked motion artifacts reported by Clauser et al (9). This relatively low rate of motion artifacts should be considered as linked to the patient prone position used in state-of-the-art breast MRI that minimizes respiratory movement (13).…”
Section: Discussionsupporting
confidence: 75%
“…Our motion artifacts rate (35%) was intermediate between the 16% reported by Fiaschetti et al (12) and the 46% reported by Clauser et al (9). This may reflect different kind of considered motion artifacts, as Fiaschetti et al (12) reported artifacts affecting image interpretation, without any grading scale.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, the fast acquisition time makes DWI less susceptible to motion artifacts. The latter can be challenging in the interpretation of the DP [32]. Finally, the quantitative nature of the ADC is not without controversy, and there is ongoing research how to achieve more exact measurement using dedicated phantoms [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we highlight that our intermediate screening setting implied an expected low cancer detection rate: researchers had to reckon also with this expectation, trying to minimize unnecessary biopsies and overdiagnosis [ 13 , 45 , 46 , 47 ]. Finally, researchers had also to be aware of the peculiar spectrum of potential false-positive and false-negative findings, for example, those engendered by motion artifacts [ 48 ] and by the influence of background parenchymal enhancement [ 49 , 50 ], which are commonly associated with MRI. As mentioned above, general countermeasures to curtail them, such as the repetition of MX or the use of targeted US, were implemented in this study and will be the object of specific analysis.…”
Section: Discussionmentioning
confidence: 99%